(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the role and importance of interactive teaching methods in developing students’ creative abilities in the higher education system. In the modern educational process, the formation of students’ independent thinking, creative approach to problem situations, the development of new ideas, and the formation of innovative decision-making competencies is considered an important pedagogical task.